2009
DOI: 10.1210/jc.2009-0053
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Gender, Obesity, and Muscle Lipase Activity on Intramyocellular Lipids in Sedentary Individuals

Abstract: These data suggest that intramyocellular DAG is an independent predictor of insulin resistance in humans and that its levels correlate with lipolytic enzymes activity in skeletal muscle but not with markers of adiposity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
114
2
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 132 publications
(132 citation statements)
references
References 38 publications
14
114
2
1
Order By: Relevance
“…Six young healthy subjects, mean age 22.9 ± 0.4 yrs (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29) and mean BMI 26.5 ± 0.5 kg/m 2 (20.1-34.7) were recruited in the study. The protocol was approved by the institutional review board of the Pennington Biomedical Research Center, and all volunteers gave written informed consent.…”
Section: Subjectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Six young healthy subjects, mean age 22.9 ± 0.4 yrs (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29) and mean BMI 26.5 ± 0.5 kg/m 2 (20.1-34.7) were recruited in the study. The protocol was approved by the institutional review board of the Pennington Biomedical Research Center, and all volunteers gave written informed consent.…”
Section: Subjectsmentioning
confidence: 99%
“…Triacylglycerol hydrolase (TAGH) activity was measured on tissue and cell lysates as previously described ( 19 ). Briefl y, tissue and cell lysates were extracted in a lysis buffer containing 0.25 M sucrose, 1 mM EDTA, 1 mM DTT, 20 µg/ml leupeptin, and 2 µg/ml antipain.…”
Section: Lipase Activity Assaysmentioning
confidence: 99%
“…Importantly, the impaired fatty acid oxidation can lead to the accumulation of specific IMCL intermediates, including long-chain fatty acyl-CoA, diacylglycerol and ceramide, as well as IMCL. 24 Recent studies have revealed that the accumulation of IMCL intermediates might impair insulin signaling 25 and the mitochondrial function. 26 Therefore, IMCL might have a major role in the pathogenesis of insulin resistance.…”
Section: Control Metsmentioning
confidence: 99%
“…The general perception has been that insulin resistance can be attributed to the accumulation of diacylglycerol (DAG) in liver and skeletal muscle (3)(4)(5). The mechanism by which DAG is believed to cause insulin resistance is by the activation of protein kinase C (PKC) e and PKC u leading to phosphorylation and inhibition of insulin receptor substrate 1 and the insulin signaling cascade in both liver (6,7) and skeletal muscle (8)(9)(10).…”
mentioning
confidence: 99%